Morphological status of the liver of offspring born from mothers with toxic liver lesions (Texas Journal of Medical Science, 2024)
Chronic toxic damage to the mother's liver negatively affects the processes of postnatal development and the formation of the offspring's liver. In the vascular-tissue structures of the liver of the offspring in the early periods of postnatal development, inflammatory-reactive and dystrophic changes are observed. These morphological changes in the liver of the offspring subsequently led to a slowdown and lag in the rate of growth and development and formation of the vascular-tissue structures of the liver of the offspring, compared to the offspring of control intact animals.